FACTORS AFFECTING FOOD SECURITY IN RURAL AREAS IN YOGYAKARTA PROVINCE - Susilo, Y. Sri (Journal of Indonesian Economy and Business, 2010)
The purpose of this research is to identify and analyze the factors influencing the food security of rural society in the Province of Daerah Istimewa Yogyakarta (DIY). Thelocation included several sub districts in the Regency of Sleman, Bantul, Kulon Progo, and Gunungkidul. Data utilized in this research were primary and secondary data. Primarydata were compiled by survey and interviews. Secondary data were compiled from various publication sources. Data analyzed with multinomial logit regression model.Factors influencing the food security of rural society in the Province of Daerah Istimewa Yogyakarta are based on three basic groups that are economy (income), socioculture(gender, kind of food, way of fertilization, technique of cultivation and knowledge of ecology) and ecology (land capability, land suitability, irrigation) ceteris paribus. Thethree factors cannot be separated in the equilibrium of eco-economy, eco-culture and ecology models.Keywords: food security, rural society, multinomial logit, DIY.